Relationship between maternal Vitamin D levels and neonatal Vitamin D levels with delayed neonatal hypocalcemia - A hospital-based observational study - Aasif Aziz Wani; Bhat, Mohd Ashraf; Showkat Hussain Tali (Asian Journal of Medical Sciences, 2023)
Background: Vitamin D has important role in regulating various metabolic processes in the body including calcium metabolism. Fetuses and neonates are dependent on their mothers to get adequate supply of Vitamin D. Maintaining adequate maternal Vitamin D levels may be highly beneficial for their fetuses and the babies. Aims and Objectives: The aim of the study was to find a correlation, if any, between maternal Vitamin D status and neonatal Vitamin D levels and delayed neonatal hypocalcemia. Materials and Methods: Fifty mother infant pairs with neonatal late onset hypocalcemia were included in the study. Detailed clinical history along with simultaneous maternal and neonatal blood samples were taken for estimation of calcium, phosphorus, parathormone (intact), and Vitamin D levels. Results: Mean maternal and neonatal serum Vitamin D (25-OH Vitamin D) levels were 19.5±7.5 and 15±8.5, respectively. There was a statistically significant correlation between maternal and neonatal Vitamin D levels (P=0.001). There was also a direct correlation between low maternal Vitamin D levels and delayed hypocalcemia in neonates (P=0.048). Mean maternal and neonatal serum calcium levels were 9±1.5 mg/dl and 6.2±0.4 mg/dl, respectively. There was no significant statistical correlation between the two (P>0.05). Conclusion: Maternal Vitamin D level appears to be an important determinant of neonatal Vitamin D and serum calcium levels.